2008
DOI: 10.1111/j.1574-695x.2008.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatumenhances invasion of human gingival epithelial and aortic endothelial cells byPorphyromonas gingivalis

Abstract: Invasion by Porphyromonas gingivalis has been proposed as a possible mechanism of pathogenesis in periodontal and cardiovascular diseases. Porphyromonas gingivalis have direct access to the systemic circulation and endothelium in periodontitis patients by transient bacteremia. Periodontitis can be described as one of the predominant polymicrobial infections of humans. In the present study, P. gingivalis strains were tested for their ability to invade a human gingival epithelial cell line (Ca9-22) and human aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 49 publications
2
109
0
4
Order By: Relevance
“…Galactose, however, only partially inhibited F. nucleatum enhanced P. gingivalis invasion [10]. Furthermore, the enhancement of P. gingivalis invasion was not observed for co-infection with A. actinomycetemcomitans, that can also coaggregate with F. nucleatum [22].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Galactose, however, only partially inhibited F. nucleatum enhanced P. gingivalis invasion [10]. Furthermore, the enhancement of P. gingivalis invasion was not observed for co-infection with A. actinomycetemcomitans, that can also coaggregate with F. nucleatum [22].…”
Section: Discussionmentioning
confidence: 87%
“…In our previous experiments, we found that there was a modest increase in the invasion efficiencies of P. gingivalis with increasing MOI. Invasion reached a plateau at about 100 MOI [10] . Thus, we used MOI of 100 in all subsequent experiments.…”
Section: Monomicrobial Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodontitis has been considered to be a biofilm infection 3,17,19) , and the polymicrobial nature of the periodontopathic bacteria in periodontal lesions has received particular attention 7,19,20) . The results of this study indicate that the relationships between coexistence of P. gingivalis, T. forsythia and T. denticola, designated the red complex, and PD or BOP were significant in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Le parodonte représente une « porte d'entrée » pour les agents infectieux parodontaux tels que Actibacillus actinomycetemcomitans et Porphyromonas gingivalis qui ont la capacité d'envahir les cellules épithéliales. Après leur internalisation, ces bactéries à majorité Gram né-gatif sont capables de franchir la membrane cytoplasmiques des cellules adjacentes entrainant une bactériémie [24] et une élévation des paramètres inflammatoires. On observe ainsi une augmentation de la CRP induite par la stimulation de l'interleukine 1-beta (IL1-beta) ou du TNF alpha [25,26] par le LPS.…”
Section: Introductionunclassified